PERAN BAPPELITBANGDA DALAM MENDORONG INOVASI DAN PENGEMBANGAN EKONOMI LOKAL DI KOTA BANJAR - Astuti , Puji; Farizan, Akmal; Azhayr, Muhammad Naufal Azhayr; Aditiya, Eva Charena Aditiya; Irfan Nursetiawan (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
In March 2020, Indonesia was shocked by a terrible virus, the Covid-19 pandemic. Until August, Covid-19 in Indonesia reached 165,887 including 7,169 deaths covering 34 provinces. Then the Covid-19 outbreak had an impact on the decline in economic activity of MSMEs in Indonesia, especially Banjar City. The purpose of this study was to find out about the role of the Regional Planning, Research, Development Agency (BAPPELITBANGDA) when formulating Technical Policies for Regional Development Planning Research in Banjar City and the factors that affect the Economy in Banjar City caused by Covid-19 and increasing Innovation in economic development in Banjar City. The people of Banjar City cannot carry out their usual activities due to the government’s appeal to set policies for WFH (Work from Home) and Social Distancing. Therefore, BAPPELITBANGDA made an innovation design that will be developed in stages which is expected to overcome the decline in the economy in Banjar City. This study uses direct observation techniques using the interview method, researchers visit the places studied and researchers obtain other sources through the official BAPPELITBANGDA website as a source of research data that supports observations.